Application of a ω-3 Desaturase with an Arachidonic Acid Preference to Eicosapentaenoic Acid Production in Mortierella alpina - Ge, Chengfeng; Chen, Haiqin; Mei, Tiantian; Tang, Xin; Chang, Lulu; Gu, Zhennan; Zhang, Hao; Chen, Wei; Chen, Yong Q. (Frontiers in Bioengineering and Biotechnology, 2018)
In the industrial oleaginous fungus Mortierella alpina, the arachidonic acid (AA; C20:4; ω-6) fraction can reach 50% of the total fatty acids in vivo. However, the eicosapentaenoic acid (EPA; C20:5; ω-3) fraction is less than 3% when this fungus is cultivated at a low temperature (12°C). Omega-3 fatty acid desaturase is a key enzyme in ω-3 long-chain polyunsaturated fatty acids (LC-PUFAs) biosynthesis pathways. To enhance EPA production, we transformed the ω-3 fatty acid desaturase (PaD17), which exhibits strong Δ-17 desaturase activity, into Mortierella alpina, thus increasing the AA to EPA conversion rate to 49.8%. This PaD17-harbouring Mortierella alpina reconstruction strain produced 617 mg L-1 of EPA at room temperature in broth medium, this yield was increased to 1.73 g L-1 after culture medium optimisation, (i.e., about three fold higher than that under original culture conditions), with concomitant respective increases in dry cell weight and total fatty acids content to 16.55 g L-1 and 6.46 g L-1. These findings suggest a new platform for the future industrial production of EPA.